CATHETER DURATION AND THE RISK OF SEPSIS IN PREMATURE BABIES WITH UMBILICAL VEIN CATHETERS - Hartojo, Hartojo; Utomo, Martono Tri (Institute of Topical Disease Universitas Airlangga, 2012)
Umbilical catheters are frequently required in the management of severely ill premature babies. The risk of complications may increase with duration of UVC use. Objective: To determine whether the risk of central line-associated bloodstream infections (CLA-BSIs) and sepsis remained constant over the duration of umbilical vein catheters (UVCs) in high-risk premature neonates.Methods:retrospective analysis. The data were collected from the medical record of high risk premature neonates who had a UVC placed in neonatal care unit of Husada Utama Hospital between April 1st 2008 to April 30th 2011 with purposive sampling. Catheter duration was observed before and after 14 days on placement. Blood and UVC culture was performed to establish the risk of CLA-BSIs and sepsis. Chi-square and logistic regression analysis were performed in the laboratorium data. Result: A total 44 high risk premature babies with UVCs were enrolled (sepsis group: n = 23 and non sepsis group: n = 21). Baseline demographics were similar between the groups. 15 babies in sepsis group have UVCs duration > 14 days, and 8 babies have UVCs < 14 days (p = 0.533). Days of UVC < 14 days show UVCs culture performance in 11 babies with positive evidence, blood culture performance shows negative in 21 babies (p = 0.516). Days of UVC >14 days show blood culture performance in 11 babies with positive evidence, UVCs culture performance is negative in 18 babies (p = 0.456). Burkholderia cepacia and Klebsiella pneumonia mostly appeared in blood culture performance. 25% of UVC culture performance shows Pseudomonas aeroginosa. Conclusions: The catheter duration have no significant differencein risk of sepsis in premature babies with Umbilical Vein Catheters.